The Analysis Study of Stem Cell Therapy for Stress Urinary Incontinence : A Comprehensive Systematic Review - Musa, Muhammad Ridwan; Semme, Muhammad Yatsrib (The International Journal of Medical Science and Health Research, 2024)
Background: Urinary incontinence is a common health problem affecting a large number of women. Approximately 35% of women over 18 years in Europe reported involuntary urine loss. Stress urinary incontinence (SUI) is the most common type, and it is defined as involuntary loss of urine on effort or physical exertion. The aim: The aim of this study to show about stem cell therapy for stress urinary incontinence. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The effect of stem cell in combination with injectable bulking agent to treat stress urinary incontinence (SUI). The treatment with autologous adiposed stem cell was shown to be safe and well-tolerated and reasonably effective.